2016
DOI: 10.1126/science.aah3429
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast electron diffraction imaging of bond breaking in di-ionized acetylene

Abstract: Visualizing chemical reactions as they occur requires atomic spatial and femtosecond temporal resolution. Here, we report imaging of the molecular structure of acetylene 9 fs after ionization. Using mid-infrared laser induced electron diffraction (LIED) we obtain snapshots as a proton departs the [C 2 H 2 ] 2+ ion. By introducing an additional laser field, we also demonstrate control over the ultrafast dissociation process and resolve different bond dynamics for molecules oriented parallel vs. perpendicular to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
249
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(251 citation statements)
references
References 62 publications
2
249
0
Order By: Relevance
“…In fact, it has been found that all the important strong-field phenomena, which involve rescattering physics, start with an ionization step [1]. Imaging techniques based on rescattering such as laser-induced electron diffraction (LIED) [2,3] and high-order harmonics spectroscopy (HHS) [4][5][6][7] are now capable of probing dynamic molecular structural changes with sub-Ångstrom spatial and few-femtosecond temporal resolutions. Correct interpretation and extraction of target structures depend critically on an accurate description of the ionization step.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been found that all the important strong-field phenomena, which involve rescattering physics, start with an ionization step [1]. Imaging techniques based on rescattering such as laser-induced electron diffraction (LIED) [2,3] and high-order harmonics spectroscopy (HHS) [4][5][6][7] are now capable of probing dynamic molecular structural changes with sub-Ångstrom spatial and few-femtosecond temporal resolutions. Correct interpretation and extraction of target structures depend critically on an accurate description of the ionization step.…”
Section: Introductionmentioning
confidence: 99%
“…Here we advance attosecond metrology to picometre wavelength and sub-atomic resolution by using free-space electrons instead of higher-harmonic photons 1-7 or re-colliding wavepackets [8][9][10][11] . A beam of 70-keV electrons at 4.5-pm de Broglie wavelength is modulated by the electric field of laser cycles into a sequence of electron pulses with sub-optical-cycle duration.…”
mentioning
confidence: 99%
“…
Attosecond spectroscopy1-7 can resolve electronic processes directly in time, but a movie-like space-time recording is impeded by the too long wavelength (~100 times larger than atomic distances) or the source-sample entanglement in re-collision techniques [8][9][10][11] . Here we advance attosecond metrology to picometre wavelength and sub-atomic resolution by using free-space electrons instead of higher-harmonic photons 1-7 or re-colliding wavepackets [8][9][10][11] .
…”
mentioning
confidence: 99%
“…They succeeded in capturing the dynamical evolution of oxygen and nitrogen structures under a vibrational excitation [96]. Recently, advances have been reported in LIED experiments performed with mid-infrared few-cycle high repetition rate parametric sources, providing the extension of this technique to the sub-Å imaging of a polyatomic molecule, such as ethylene [97,98], and to the exploration with a sub-fs resolution of a chemical process, such as bond-breaking in acetylene [99].…”
Section: Photoelectron Spectroscopymentioning
confidence: 99%